Implementasi Strategi Instagram Marketing Berbasis Model AIDA untuk Optimalisasi Konten UMKM Kuliner - Bayanussabil, Muhammad Syahid; Pramudiawardani, Shelly; Rusmanto, Rusmanto (Jurnal Informatika Terpadu, 2025)
This study aims to design and implement an Instagram marketing strategy using the AIDA model (Attention, Interest, Desire, Action) to enhance consumer purchase interest for Mie Ayam Bakso Mas Dava, a micro, small, and medium enterprise (MSME). The research employs a qualitative descriptive method, collecting data through interviews, observations, and analysis of Instagram Insights. Data were analyzed using NVivo to identify themes aligned with the AIDA model, which was validated through triangulation. The results show that the strategy was successfully designed using AIDA-based Reels, Stories, and Feed content, achieving 5,171 views, 222 interactions, and 27 Linktree clicks, as recorded in Instagram Insights from April to May 2025. Reels were the most effective format, followed by Stories and Feed. The implementation increased purchase interest through aesthetic visuals and a clear call-to-action (CTA). However, limitations such as a low follower count (53) and geographical constraints suggest the need for increased Reels frequency and Instagram Ads. This study contributes to the development of digital marketing strategies for MSMEs.